DETERMINAN PERILAKU PENGELOLAAN FOOD WASTE TENANT DI KANTIN UNIVERSITAS: PENDEKATAN THEORY OF PLANNED BEHAVIOR - Safitri, Dewi; Martha, Evi; Fitriana, Delta; Susila, Lia Rahmawati; Widya, Shinta Restyana; Zainita, Ulfi Hida (Poltekkes Kemenkes Bandung, 2025)
Food waste refers to the food discarded at both distribution and consumption stages, posing significant environmental, economic, and social challenges. In Indonesia, this issue is particularly alarming, with an estimated 23-48 million tons of food waste produced annually. Research from China identifies university cafeterias as significant contributors to food waste, underscoring the need for sustainable food waste management strategies within higher education institutions. Universities, as centers of learning and social influence, play a critical role in promoting sustainable practices, including effective food waste management. This study aimed to identify factors influencing food waste management behaviors among university cafeteria tenants using the Theory of Planned Behavior (TPB). The method used in this study was a qualitative approach with a case study design. The primary informants consist of 10 university cafeteria tenants who have been operating for at least six months. Informants were selected purposively, based on principles of adequacy and relevance. Data were gathered through Focus Group Discussions (FGDs), facilitating in-depth exploration of attitudes, subjective norms, and perceived behavioral control regarding food waste management. Findings reveal that tenants' attitudes towards food waste, social norms, and their perceived control over food management practices all significantly impact their behaviors. This study emphasizes the need for comprehensive educational programs for tenants and university policies to enhance food waste management, ultimately fostering a sustainable campus environment.